Synthesis and Spectroscopic Studies of Axially Ligated Zn(II)5,10,15,20-meso-tetra(p-chlorophenyl)porphyrin with Oxygen and Nitrogen Donors - Gauri D. Bajju; Sujata Kundan; Ashu Kapahi; Deepmala Gupta (Journal of Chemistry)
Reaction of 5,10,15,20-meso-tetra(p-chlorophenyl)porphyrin[H2(p-Cl)pp] with zinc(II)acetate(Zn(OAc)2) and phenols results in the formation of corresponding axially ligated zinc(II)-meso-tetra(p-chlorophenyl)porphyrin (X-Zn-t(p-Cl)PP) (X = phenolates and pyridinates). The four-coordinated zinc porphyrin accepts one axial ligand in 1 : 1 molar ratio to form five-coordinated complex, which is purified by column chromatography and characterized by IR spectra, 1H NMR, electronic absorption spectra, elemental analysis, mass spectroscopy, and TGA/DTA studies. IR spectra confirms the appearance of Zn– at 500–400 cm−1, Zn– at 650–570 cm−1 and Zn–O at 650–350 cm−1. 1H NMR spectra show that the protons of the Phenolic ring axially attached to the central metal ion are merged with the protons of the tetraphenyl rings of the porphyrin moiety. Absorption spectra reveal that complexes are accompanied by blue shift (hypsochromic shift) for phenolates and red shift (bathchromic shift) for pyridinates in comparison with the basic Zporphyrin emission bands. Mass Spectra determine the m/z ratio. The percentage of each element is confirmed by elemental analysis. According to the thermal studies, the complexes have a higher thermal stability and the decomposition temperature of these complexes depends on the axial ligation. The invitro antifungal activity of the complexes synthesized above had been done by disc diffusion method against the pathogen “Fusarium spp.,” which shows that with the increase in the concentration of the complexes, the colony diameter decreases and hence percent inhibition increases.